1973
DOI: 10.1021/jo00950a033
|View full text |Cite
|
Sign up to set email alerts
|

Stereochemistry of febrifugine. II. Evidence for the trans configuration in the piperidine ring

Abstract: 1.80 1.75 oc2h6 1.82 1.76 OCH(CH3)2 1.88 1.82 ch3 2.23 0.96 2.11 0.82 " 10% toluene solutions except for the 3-methyl compound which was 50% in chloroform. Chemical shifts given in (parts per million) from tetramethylsilane.A 30% solution shows the peaks shifted to 1.84 and 1.88 with incomplete resolution. The results were similar in benzene and for the other alkoxy substituents. In the case of the 3-methyl analog, the peaks were at 2.11 and 2.23 in CHC13 for the trans and cis isomers. When toluene is the solv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
9
0

Year Published

1978
1978
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(10 citation statements)
references
References 3 publications
1
9
0
Order By: Relevance
“…Ozonolysis of 4, followed by PCC oxidation afforded cis-piperidine lactone (cis-5) with a cbz group. Hydrogenolysis and benzoylation of cis-5 gave cis-3, which has the same 1 H-NMR spectrum as reported by Barringer et al 11) Each proton on the bridge-head of cis-3 in the 1 H-NMR (60 MHz) spectrum was observed at d 4.69 and 5.15 ppm, with a coupling constant of 7.7 Hz ( Table 2). …”
supporting
confidence: 79%
See 1 more Smart Citation
“…Ozonolysis of 4, followed by PCC oxidation afforded cis-piperidine lactone (cis-5) with a cbz group. Hydrogenolysis and benzoylation of cis-5 gave cis-3, which has the same 1 H-NMR spectrum as reported by Barringer et al 11) Each proton on the bridge-head of cis-3 in the 1 H-NMR (60 MHz) spectrum was observed at d 4.69 and 5.15 ppm, with a coupling constant of 7.7 Hz ( Table 2). …”
supporting
confidence: 79%
“…Subsequently, their relative 6) and absolute 7) structures were proposed, based on Baker's synthetic work. [8][9][10] The relative configuration 11) of (ϩ)-1 was corrected in 1973 and then the absolute structures 12,13) of (ϩ)-1 and (ϩ)-2 were corrected in 1999. Currently, dramatic medical [14][15][16][17] and synthetic [18][19][20][21][22][23][24][25] studies of (ϩ)-1 are in progress.…”
mentioning
confidence: 99%
“…Compound 3 or its open chain analogues b-amino-g-hydroxy carboxylates are active components of many biologically active natural products, such as antifungal/antibiotic peptides [16] and antimalarial alkaloids, [17] as well as active pharmaceuticals, such as gastroprotective drugs [18] and inhibitors of phosphodiesterase [19] and HIV-1 protease. [20] Apart from being associated with biological as well as pharmaceutical activities, this structural subunit is also used in preparing functionalized b-amino acids, [21] oxazolidinones, [22] and aziridines.…”
Section: Resultsmentioning
confidence: 99%
“…During the literature survey, it was found that the H-2 signal of febrifugine, a 3-substituted (3H)-quinazolin-4-one derivative having antimalarial activity, appeared at 8 8.91 in its hydrochloride (6). This was further confirmed by the 1H-nmr study of synthetic echinozolinone hydrochloride, in which H-2 appeared as a singlet at 8 8.90 (unpublished results).…”
mentioning
confidence: 77%